Epigenetic Modulation of Stem Cells in Neurodevelopment: The Role of Methylation and Acetylation - Podobinska, Martyna; Szablowska-Gadomska, Ilona; Augustyniak, Justyna; Sandvig, Ioanna; Sandvig, Axel; Buzanska, Leonora (Frontiers in Cellular Neuroscience, 2017)
The coordinated development of the nervous system requires fidelity in the expression of specific genes determining the different neural cell phenotypes. Stem cell fate decisions during neurodevelopment are strictly correlated with their epigenetic status. The epigenetic regulatory processes, such as DNA methylation and histone modifications discussed in this article, may impact both neural stem cell (NSC) self-renewal and differentiation and thus play an important role in neurodevelopment. At the same time, stem cell decisions regarding fate commitment and differentiation are highly dependent on the temporospatial expression of specific genes contingent on the developmental stage of the nervous system. An interplay between the above, as well as basic cell processes, such as transcription regulation, DNA replication, cell cycle regulation, and DNA repair therefore determine the accuracy and function of neuronal connections and may significantly impact embryonic health and development as well as cognitive processes such as neuroplasticity and memory formation later in the adult.